Operations research mothods (related production distribution and inventory management applications) - Craven B.D., Islam S.M.N. (The ICFAI University Press, Hyderabad, 2006)
Commerce
ENGLISH
Keywords: Operations research mothods (related production distribution and inventory management applications); Commerce; Commerce